Estimating energy costs and greenhouse gas emissions efficiency in the provision of domestic water: An empirical application for England and wales. (October 2022) - Molinos-Senante, Maria; Maziotis, Alexandros; Mocholi-Arce, Manuel; Sala-Garrido, Ramón
HIGHLIGHTS: Specific efficiency sores for energy costs and greenhouse gas emissions were estimated. English and Welsh water companies could save 35.6% of the current energy costs. Efficiency on greenhouse gas emissions was estimated at 41.5% level. Abstract: Reducing greenhouse gas (GHG) emissions and energy costs has been one of the main challenges faced by the water sector. This study provides a quantification of energy costs and GHG emissions efficiency of a sample of the English and the Welsh water companies over the period of 2013-2018. In doing so, the multi-directional data envelopment analysis (DEA) method was employed, which allows the quantification of the potential savings in energy costs and GHG emissions, i.e. defining the targets to be set by the water regulators. In the second stage of the analysis, bootstrap techniques were applied to identify environmental variables influencing the performance of water companies. The results indicate that the efficiency of the English and the Welsh water companies was low since the average efficiency scores for energy costs and GHG emissions were 0.644 and 0.415, respectively. It reveals that the water sector might save 35.6% and 58.6% of the current energy costs and GHG emissions. The study's findings demonstrated that the source of raw water, the treatment required to produce drinking water and population density were the environmental variables influencing the efficiency of these water companies in terms of energy costs and GHG emissions. The evidence provided by this study is of great interest to water regulators and water companies to implement policies and measures towards a low-carbon urban water cycle.